A Systematic Review Supporting the American Society for Dermatologic Surgery Guidelines on the Prevention and Treatment of Adverse Events of Injectable Fillers. Issue 2 (February 2021) - Nayfeh, Tarek; Shah, Sahrish; Malandris, Konstantinos; Amin, Mustapha; Abd-Rabu, Rami; Seisa, Mohamed O.; Saadi, Samer; Rajjoub, Rami; Firwana, Mohammed; Prokop, Larry J.; Murad, Mohammad H.
Abstract : BACKGROUND: As the use of injectable skin fillers increase in popularity, an increase in the reported adverse events is expected. OBJECTIVE: This systematic review supports the development of American Society for Dermatologic Surgery practice guideline on the management of adverse events of skin fillers. METHODS AND MATERIALS: Several databases for studies on risk factors or treatments of injection-related visual compromise (IRVC), skin necrosis, inflammatory events, and nodules were searched. Meta-analysis was conducted when feasible. RESULTS: The review included 182 studies. However, IRVC was very rare (1–2/1, 000, 000 patients) but had poor prognosis with improvement in 19% of cases. Skin necrosis was more common (approximately 5/1, 000) with better prognosis (up to 77% of cases showing improvement). Treatments of IRVC and skin necrosis primarily depend on hyaluronidase injections. Risk of skin necrosis, inflammatory events, and nodules may be lower with certain fillers, brands, injection techniques, and volume. Treatment of inflammatory events and nodules with antibiotics, corticosteroids, 5-FU, and hyaluronidase was associated with high response rate (75%–80%). Most of the studies were small and noncomparative, making the evidence certainty very low. CONCLUSION: Practitioners must have adequate knowledge of anatomy, elicit history of skin filler use, and establish preemptive protocols that prepare the clinical practice to manage complications. Abstract : Supplemental Digital Content is Available in the Text.